2001
DOI: 10.1073/pnas.151147098
|View full text |Cite
|
Sign up to set email alerts
|

Specific repression of β-globin promoter activity by nuclear ferritin

Abstract: Developmental hemoglobin switching involves sequential globin gene activations and repressions that are incompletely understood. Earlier observations, described herein, led us to hypothesize that nuclear ferritin is a repressor of the adult ␤-globin gene in embryonic erythroid cells. Our data show that a ferritin-family protein in K562 cell nuclear extracts binds specifically to a highly conserved CAGTGC motif in the ␤-globin promoter at ؊153 to ؊148 bp from the cap site, and mutation of the CAGTGC motif reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…These include (12) sequencing of cDNA clones, which shows identity with chicken reticulocyte ferritin (39); immunoblotting of nuclear and cytoplasmic fractions of CE cells; immunofluorescence with a number of monoclonal and polyclonal antibodies against the H-chain of ferritin; and electrophoretic behavior of the supramolecular complex under non-denaturing conditions. The only other reports of nuclear ferritin have been in pathological conditions and in K562 cells, in which a ferritin-like protein has been suggested to function in gene regulation (42,43). Thus, to our knowledge, the CEnuclear ferritin is the only example in normal cells in which a cytoplasmic molecule undergoes nuclear transport in a tissuespecific and essentially quantitative manner.…”
Section: Discussionmentioning
confidence: 99%
“…These include (12) sequencing of cDNA clones, which shows identity with chicken reticulocyte ferritin (39); immunoblotting of nuclear and cytoplasmic fractions of CE cells; immunofluorescence with a number of monoclonal and polyclonal antibodies against the H-chain of ferritin; and electrophoretic behavior of the supramolecular complex under non-denaturing conditions. The only other reports of nuclear ferritin have been in pathological conditions and in K562 cells, in which a ferritin-like protein has been suggested to function in gene regulation (42,43). Thus, to our knowledge, the CEnuclear ferritin is the only example in normal cells in which a cytoplasmic molecule undergoes nuclear transport in a tissuespecific and essentially quantitative manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that a ferritin family protein in K562 nuclear extracts binds specifically to the CAGTGC motif in the ␤-globin promoter at bp Ϫ153 to Ϫ148 (12). In the same study, recombinant ferritin H protein was shown to bind to this sequence in a sequence-specific manner, and transfection of the ferritin H expression plasmid into CV-1 cells repressed the ␤-globin promoter in reporter assays (12). On the other hand, results contradictory to these observations were also reported, in which the presence of ferritin in the nucleus of K562 cells was confirmed and an antiferritin antibody blocked protein binding to a ␤-globin promoter region; however, the protein was heat sensitive, with a molecular mass of 90 to 100 kDa, and also, recombinant ferritin H or L failed to bind to the ␤-globin promoter (53).…”
mentioning
confidence: 88%
“…Using gel mobility shift assays in K562 erythroleukemic cells, Broyles and coworkers demonstrated specific binding of a protein with properties of ferritin H to a conserved CAGTGC motif in the beta globin promoter. 135 Transient transfection assays revealed that ferritin H repressed synthesis of beta globin, suggesting that ferritin may play a role in hemoglobin switching. Although a nuclear distribution and function for ferritin has not been unequivocally documented, the accumulation of reports of nuclear ferritin localization needs careful attention, 136,137 particularly given the report of an E coli protein structurally related to ferritin that binds to and protects DNA from oxidative damage.…”
Section: New Roles For Ferritin In Heme Synthesis?mentioning
confidence: 99%